Kajian Reka Bentuk Majalah: Rhythms Of The Third World (ROTTW)' - Suhaina, Ab Rahman (Universiti Malaysia Sarawak, (UNIMAS), 2006)
'Rhythms Of The Third World' (ROTTW) is a Malaysia own infotaiment magazine in Malay languageversion. This magazine has been in the market for several years but not been widely exposed to the readers especially in past Malaysia. This research is conducted to study the element of graphics that are being used in the publication of the magazine. The objective of this research is to identity the weeknesses of the magazine and the perception of readers towards the magazine design. This is for banchmark designing a new Malay language version of local designers magazine. Some recomendations for the new inforainment design magazine will also be discussed.